Analyzing Misconceptions of Acid-Base Topic among Chemistry Education Students in Online Learning Settings: A Case Study - Catur Fathonah Djarwo; Frans Pither Kafiar (Universitas Pendidikan Mandalika, 2023)
This study aims to identify the misconceptions of 11 third semester Chemistry Education students at Cenderawasih University in relation to online learning during the Covid-19 pandemic. Online learning poses various challenges for both students and lecturers, resulting in incomplete explanations and hindering students' understanding of the material, leading to possible misconceptions. A descriptive qualitative method was employed, utilizing diagnostic tests with a Certainty or Response Index (CRI) and interviews. The findings revealed that 41% of the students had a clear understanding of the acid-base concepts, 30% lacked understanding, and 29% had misconceptions. The students' misconceptions related to six subconcepts in acid-base materials, including acid-base theory, acid-base indicators, acid strength (pH), weak acid-base equilibrium constant (Ka/Kb), calculation of solution pH, and the concept of pH in the environment, with a range of misconceptions from 9-45%. This study highlights the need for addressing misconceptions in online learning, specifically in the acid-base topic, to ensure effective understanding and learning outcomes for students.